THE IMPACT OF THE LEADERSHIP, MOTIVATION AND JOB SATISFACTION TOWARDS EMPLOYEES PERFORMANCE IN ONE OF FINANCING COMPANY IN INDONESIA - Sadewo, Dandika; Chaerudin, Chaerudin (Dinasti International Journal of Management Science, 2021)
This research has purposed to revealed those impact from the leadership, motivation and job satisfaction on employee performance in one of finance company in Indonesia. This research were include in qualitative descriptive research with the population are all employees of that finance company in Indonesia, which amounted of 405 employees, the sampling technique used proportional random sampling with a sample size of 80 respondents. The data collected through questionnaires. The data analysis method that used is multiple linear regression analysis to examine the hypothesis. According to these data analysis, the results shows that leadership, motivation and job satisfaction had a positive and significant affect on employee performance.